Comparación de las propiedades de osteoconducción y osteointegración de una hidroxiapatita reabsorbible comercial con una hidroxiapatita reabsorbible sintetizada - Jaramillo, Carlos D.; Rivera Posada, Jairo A.; Echavarría, Alejandro; O¨byrne, Johan; Congote, Diego; Restrepo, Luis F. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In the following article the effects of two types of hydroxiapatites on bone synthesis and properties were evaluated. One of them (OseoU) was synthesized at two different temperatures to compare it to a commercial mixture of hydroxiapatite (Osteogen®) commonly used in several surgical procedures in which loss of bone tissue is present. The synthesis was carried out in the laboratories of the Universidad de Antioquia by precipitating the mixture of calcium nitrate and ammonium phosphate. The final products and the commercial hydroxiapatite were characterized by sweeper electronic microscopy (SEM), X ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR), and energy dispersed spectrometry (EDS). The properties of osteoconduction and osteointegration were measured according to the capacity of the products to induce the differentiation of local cells into bone forming cells. Such characteristics were evaluated in hydroxiapatite implants in 70 New Zealand breed rabbits distributed in seven groups, ten rabbits in each group, which were evaluated at days 7, 14, 21, 28, 42, 60 and 90 after the surgical procedure. The results demonstrated that the hydroxiapatites synthesized in the laboratories of the Universidad de Antioquia and the commercial hydroxiapatite showed similar characteristics in terms of the crystal structure, chemical composition and absorption properties with slight morphological differences in particle shape and size. Using variance analysis, no meaningful statistical differences were found between the histopathological variables evaluated in the several hydroxiapatite groups (p>0.05), indicating that results obtained with both the OseoU and the commercial hydroxiapatite equally affected bone synthesis and properties.